Optimal oncologic management and mTOR inhibitor introduction are safe and improve survival in kidney and liver allograft recipients with de novo carcinoma. Issue 4 (20th November 2018) - Rousseau, Benoit; Guillemin, Aude; Duvoux, Christophe; Neuzillet, Cindy; Tlemsani, Camille; Compagnon, Philippe; Azoulay, Daniel; Salloum, Chaddy; Laurent, Alexis; de la Taille, Alexandre; Salomon, Laurent; Cholley, Irène; et al.
Abstract : Prognosis and oncologic treatment feasibility in solid organ transplant patients with de novo cancer remain poorly described. We investigated the impact of immunosuppressive therapy modifications after de novo cancer diagnosis on oncologic treatment feasibility, toxicities, and prognosis. Patients with de novo cancer (excluding nonmelanoma skin cancers) were selected from a monocentric cohort of 4, 637 kidney and liver allograft recipients. We assessed oncologic treatment optimality according to guidelines and analyzed immunosuppressive drug modifications and oncologic treatment impacts on treatment feasibility, toxicities, and graft/patient survivals. A total of 180 patients with 205 cancers were included: mean age 60 years, median delay from transplantation to first de novo cancer 5 years. In 46% of cases, immunosuppressive therapy was modified after cancer diagnosis: 24% dose reduction and 22% mTOR inhibitor introduction. Optimal oncologic treatment was performed in 80% and 38% of patients with localized and advanced cancer respectively. Transplantation and immunosuppression hindered optimal oncologic treatment in 11% instances. Immunosuppressive therapy modifications did not affect oncologic treatment tolerance nor graft survival. In multivariate analysis, optimal oncologic treatment and mTOR inhibitor introduction improved survival of patients with de novo carcinoma. Optimal oncologic treatment is feasible in kidney and liver allograft recipients without safety concerns. Optimal oncologic treatment and mTOR inhibitor introduction seem to markedly improve survival of patients with de novo carcinoma. Abstract : What's new? Risk of cancer after solid organ transplantation is increased, in part due to immunosuppressive treatments modifying the balance between immune tolerance and anti‐tumoral immunity. mTOR inhibitors, which today are used either as an immunosuppressive agent to prevent graft rejection or an anti‐tumor drug, have shown therapeutic promise for these patients, however. In this large well‐documented cohort, immunosuppression dose reduction does not translate into overall survival benefit. Rather, optimal oncological treatment and introduction of a mTOR inhibitor at immunosuppressive doses are feasible without safety concerns in solid organ transplant patients presenting with de novo carcinoma, and dramatically improve patient overall survival.